2021
DOI: 10.4103/jgid.jgid_224_20
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Salmonella meningitis and Hemophagocytic Lymphohistiocytosis

Abstract: Enteric fever is a common infectious disease of the tropical world. Common age group involved is children aged between 5 and 10 years. In addition to diarrhea, it may lead to extraintestinal infections including aseptic meningitis, hepatitis, cholecystitis, acute abdomen, intestinal perforation, pneumonia, psychosis, and ataxia. Hematologic complications leading to hemophagocytosis have a prevalence of < 1%. Salmonella meningitis has an incidence of 6% with poor prognosis neurological se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several researchers have shown that antimicrobial and supportive treatment alone are effective[ 5 , 19 - 23 ]. However, many researchers have used both antimicrobial treatment and the HLH protocol to treat sHLH triggered by Salmonella infections[ 6 , 10 , 24 ]. In this study, after careful evaluation, our patient did not receive HLH chemotherapy during the whole disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have shown that antimicrobial and supportive treatment alone are effective[ 5 , 19 - 23 ]. However, many researchers have used both antimicrobial treatment and the HLH protocol to treat sHLH triggered by Salmonella infections[ 6 , 10 , 24 ]. In this study, after careful evaluation, our patient did not receive HLH chemotherapy during the whole disease course.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, HLH secondary to typhoidal Salmonella infection has been reported in a few cases. One case report described a previously healthy four-year-old girl with HLH secondary to Salmonella typhi [ 9 ] and another case report discussed a rare presentation of typhoid fever with meningitis and secondary HLH in a previously healthy five-year-old child [ 10 ]. Both patients in the above-mentioned case reports had no evidence of immune deficiencies [ 9 - 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…One case report described a previously healthy four-year-old girl with HLH secondary to Salmonella typhi [ 9 ] and another case report discussed a rare presentation of typhoid fever with meningitis and secondary HLH in a previously healthy five-year-old child [ 10 ]. Both patients in the above-mentioned case reports had no evidence of immune deficiencies [ 9 - 10 ]. The severe presentation in our patient seems to be due to the underlying IL12Rβ1 deficiency, which selectively predisposes the affected individual to infections with non-typhoidal Salmonella among other intracellular pathogens [ 3 ].…”
Section: Discussionmentioning
confidence: 99%